Calculated in Death - Robb, J. D., 1950- (Robb, J. D., 1950- In death novel., 2013)
When Marta Dickenson, a well-off accountant and a beloved wife and mother, is murdered, Lieutenant Eve Dallas immerses herself in her billionaire husband Roarke's world of big business to discover who arranged a hit on an innocent woman.